Thread of Blood - Fernández de Castro, Patricia (Frontera Norte, 2017)
Ana María Alonso Thread of Blood. Colonialism, Revolution and Gender on Mexico’s Northern Frontier. Hegemony and Experience: Critical Studies in Anthropology and History. Tucson, University of Arizona Press, 1995, xi, 303 pp.